Perubahan Wazan Syair “Ya Syi’ru” Karya Abu Al-Qasim Al-Syabi - Sarif udin (Pusat Studi Kependidikan (PSKp) Fakultas Ilmu Tarbiyah dan Keguruan, Universitas Sains Al-Qur'an, 2020)
The history of Arabic literature has revealed that the custom of the Arabs in general is to enjoy composing poetry. There are also various forms of traditional poetry, Absolute poetry and free poetry. To know the truth, damage and changes that occur in the poetry wazan needed ilmu Arūḍ science. In analyzing Arabic poetry, it cannot be done haphazardly, accuracy and skill in the ‘Arūd are needed. This needs to be considered because in order to get best analysis results. The purpose of this study is to describe the types of baḥr, zihāf and illat in the poetry ya syi'ru by Syabi, in accordance with the Arūḍ Science approach. this research uses descriptive qualitative method. Data collection techniques using literature study. the data in this study are words or sentences obtained from the poem entitled ya syi'ru. The data obtained are classified and analyzed by descriptive methods, according to the type of data obtained. The results showed that the type of baḥr used in the poems of ya syi'ru by Syabi is baḥr Majzu’ Kamil, Zihāf found in these poems is Iḍmar, zihāf jari majra illat (iḍmar). Zihāf who dominates in these verses is iḍmar. And the Illat found from the poem is illat tażyīl and tarfil. The most commonly found illat is illat tażyīl.